2022
DOI: 10.1002/bit.28236
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening of optimal process conditions using model predictive control

Abstract: Modern biotechnological laboratories are equipped with advanced parallel mini‐bioreactor facilities that can perform sophisticated cultivation strategies (e.g., fed‐batch or continuous) and generate significant amounts of measurement data. These systems require not only optimal experimental designs that find the best conditions in very large design spaces, but also algorithms that manage to operate a large number of different cultivations in parallel within a well‐defined and tightly constrained operating regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…[ 62 ] Here, chemostats were operated with a gradual change in dilution rate. The automated mini‐bioreactor platform developed by the TU Berlin combines robotic liquid controllers for complex feeding profiles [ 63 ] with advanced model predictive control, [ 64 ] thereby trading off between throughput and process control. The Robot Scientist by the group of Ross King is yet another example of high throughput automation where experimental space can be covered much more efficiently.…”
Section: Opportunities For Emerging Microbioreactor Technologiesmentioning
confidence: 99%
“…[ 62 ] Here, chemostats were operated with a gradual change in dilution rate. The automated mini‐bioreactor platform developed by the TU Berlin combines robotic liquid controllers for complex feeding profiles [ 63 ] with advanced model predictive control, [ 64 ] thereby trading off between throughput and process control. The Robot Scientist by the group of Ross King is yet another example of high throughput automation where experimental space can be covered much more efficiently.…”
Section: Opportunities For Emerging Microbioreactor Technologiesmentioning
confidence: 99%
“…[14][15][16][17][18] Academic literature has a few examples for the application of sensor networks and Smart Sensors in a biolab, which rely on a potpourri of systems, each equipped with sensors running in parallel forming a highly parallelized mesh of experiments. [19][20][21][22][23][24][25] In modern biolabs, sensors and devices are subjected to a diverse array of requirements. Requirements for sensor-based devices, as identified by various authors, include a wide range of features.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sinner et al (2022) reported an increase in the maximum growth rates for some substrates of a continuous process of Corynebacterium glutamicum growing on spent sulfite liquor, whereas Neubauer et al (2003) reported a decrease in glucose uptake after induction of recombinant protein production in an Escherichia coli fed‐batch process. Hence, adaptive approaches considering variations in model parameter changes during the bioprocess are needed to cope with the reduced description capabilities of tractable process models (Cruz Bournazou et al, 2016; Krausch et al, 2022; Sinner et al, 2022). For this reason, online monitoring of the biomass concentration is essential to have an accurate estimate of both, the current biomass concentration and the growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…The added value of the tool is demonstrated in the redesign of the feed rate in the exponential feeding phase and after induction of recombinant protein production. Mears et al (2017) presented an overview on feed control strategies, including the popular generic model‐based control by feedback linearization (Abadli et al, 2021; Kager, Bartlechner, et al, 2022; Kager, Horst, et al, 2022) and model‐predictive control (Kawohl et al, 2007; Krausch et al, 2022; Waldraff et al, 1997). These allow the direct control of specific rates or the further definition of constraints.…”
Section: Introductionmentioning
confidence: 99%